Access to credit and economic well-being of rural households: Evidence from Eastern India - Kumar, Anjani; Mishra, Ashok K.; Sonkar, Vinay Kumar; Saroj, Sunil (Western Agricultural Economics Association, 2020)
We evaluate the impact of access to credit on rural households’ per capita annual income using an endogenous switching regression approach, an increasingly popular method of tackling the selection bias issue in impact analyses. Using a large survey of rural households in eastern India, we find that access to credit is strongly associated with rural households’ socioeconomic and demographic characteristics. Additionally, access to credit increases rural households’ economic well-being; nonborrower rural households would benefit the most from access to credit. Access to credit affects recipients heterogeneously, implying that credit policies should be adaptable to different rural household groups.